Adaptation and implementation of the WHO Safe Childbirth Checklist around the world - Rose L. Molina (Implementation Science Communications, 2021)
Abstract Background The World Health Organization (WHO) published the WHO Safe Childbirth Checklist in 2015, which included the key evidence-based practices to prevent the major causes of maternal and neonatal morbidity and mortality during childbirth. We assessed the current use of the WHO Safe Childbirth Checklist (SCC) and adaptations regarding the SCC tool and implementation strategies in different contexts from Africa, Southeast Asia, Europe, and North America. Methods This explanatory, sequential mixed methods study—including surveys followed by interviews—of global SCC implementers focused on adaptation and implementation strategies, data collection, and desired improvements to support ongoing SCC use. We analyzed the survey results using descriptive statistics. In a subset of respondents, follow-up virtual semi-structured interviews explored how they adapted, implemented, and evaluated the SCC in their context. We used rapid inductive and deductive thematic analysis for the interviews. Results Of the 483 total potential participants, 65 (13.5%) responded to the survey; 55 completed the survey (11.4%). We analyzed completed responses from those who identified as having SCC implementation experience (n = 29, 52.7%). Twelve interviews were conducted and analyzed. Ninety percent of respondents indicated that they adapted the SCC tool, including adding clinical and operational items. Adaptations to structure included translation into local language, incorporation into a mobile app, and integration into medical records. Respondents reported variation in implementation strategies and data collection. The most common implementation strategies were meeting with stakeholders to secure buy-in, incorporating technical training, and providing supportive supervision or coaching around SCC use. Desired improvements included clarifying the purpose of the SCC, adding guidance on relevant clinical topics, refining items addressing behaviors with low adherence, and integrating contextual factors into decision-making. To improve implementation, participants desired political support to embed SCC into existing policies and ongoing clinical training and coaching. Conclusion Additional adaptation and implementation guidance for the SCC would be helpful for stakeholders to sustain effective implementation.